2020
DOI: 10.1155/2020/8825870
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Reanalysis and Satellite-Based Surface Net Radiation Data in the Arctic

Abstract: In this study, we compared four net radiation products: the fifth generation of European Centre for Medium-Range Weather Forecasts atmospheric reanalysis of the global climate (ERA5), National Centers for Environmental Prediction (NCEP), Clouds and the Earth’s Radiant Energy System Energy Balanced and Filled (EBAF), and Global Energy and Water Exchanges (GEWEX), based on ground observation data and intercomparison data. ERA5 showed the highest accuracy, followed by EBAF, GEWEX, and NCEP. When analyzing the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…The newly developed ERA5 is a state‐of‐the‐art reanalysis dataset, and its data assimilation system and model physics have been improved based on the previous version, ERA‐Interim (Hersbach et al, 2020). Previous studies have shown that ERA5 is highly accurate in Arctic regions (Seo et al, 2020). The ERA5 dataset has been widely used to evaluate climatic and environmental changes in the Arctic (Chen et al, 2022; Park et al, 2020).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The newly developed ERA5 is a state‐of‐the‐art reanalysis dataset, and its data assimilation system and model physics have been improved based on the previous version, ERA‐Interim (Hersbach et al, 2020). Previous studies have shown that ERA5 is highly accurate in Arctic regions (Seo et al, 2020). The ERA5 dataset has been widely used to evaluate climatic and environmental changes in the Arctic (Chen et al, 2022; Park et al, 2020).…”
Section: Methodsmentioning
confidence: 96%
“…Previous studies have shown that ERA5 is highly accurate in Arctic regions (Seo et al, 2020). The ERA5 dataset has been widely used to evaluate climatic and environmental changes in the Arctic (Chen et al, 2022;Park et al, 2020).…”
Section: Investigation Of the Relationship Between Thaw Dates And Veg...mentioning
confidence: 99%
“…The accumulated snowfall from ERA5 was generally comparable to the observed snow water equivalent from buoys in most cases during the accumulation period in the Arctic (C. Wang et al., 2019). For the ERA5 net radiation data, the RMSE was 19.02 W/m 2 , and the bias of −0.26 W/m 2 was low, indicating the highest accuracy among the four reanalysis products (Seo et al., 2020). In other words, the above ERA5 data could be used as validation data for CMIP6 models.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of atmospheric and oceanic data were synthesized to examine the large-scale energy budget of the Arctic. Surface radiation was verified by in situ data and an inter-comparison was performed between different satellite-based radiation data in the Arctic [4,[16][17][18]. Spatiotemporal analyses of the Arctic surface radiation budget have been synthesized using various spatial data [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of longwave, analyses of clouds and sea ice were carried out, among which many studies of longwave downwelling have been carried out [22,23,[32][33][34]. In the case of net radiation, long-term trend analysis [9,19], comprehensive research on energy budget [3], and the evaluation of products [4,17,18,35] were conducted.…”
Section: Introductionmentioning
confidence: 99%